Professionalism of Teacher: (an Overview of the Hadiths and Islamic Education Experts) - Suriadi; Dedi; Syamsuri (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2020)
Professionalism is an understanding that teaches that every job must be done by a professional person. A professional person is a person who has a profession. Furthermore, the professionalism referred to in this paper is only limited to the concept of teacher professionalism according to the viewpoint of Islamic education, which is extracted from the Hadith of the Prophet Muhammad who once stated that there are four working principles (the four principles according to the author are included in the professional element of teachers in the view of Islam) which causes someone will meet Allah with a state of joy, namely; first person who searches the world in a lawful way (man thalaba al-dunya halalan). This means that the person does work in the right way and does not violate the provisions established by the rules of Allah and his messenger. Second, people who work to keep themselves from begging (wa ta'affufan ‘an al-mas'alah). This means that the person works so as not to become a burden for other people, to get wages which are then used to meet their needs. Third, work to meet the needs of the family (wa sa'yan ‘ala 'iyalihi). A person works not only for his own interests but there are other obligations to provide for the family. Fourth, working out of compassion for one's neighbors (wa ta'athufan 'ala Jarihi), someone works to help ease the burden on others. In the thoughts of the experts of this study, they explore Al-Ghazali's thoughts, besides that, the work of Islamic education figures who explain and discuss thoughts about teachers.